2002
DOI: 10.1152/ajpheart.00191.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differential ANG II generation in plasma and tissue of mice with decreased expression of the ACE gene

Abstract: We utilized mice with homozygous disruption of angiotensin-converting enzyme (ACE) (-/-), mice with heterozygous deletion of ACE (+/-), and wild-type mice (+/+) to test the hypothesis that genetic variation in ACE modulates tissue and plasma angiotensin (ANG) II concentrations. With the use of ANG I as substrate, kidney, heart, and lung ACE activity was reduced 80% in -/- mice compared with +/+ mice. However, ANG II concentrations and ANG II-to-ANG I ratios in the kidney, heart, and lung did not differ among g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
4
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 23 publications
6
48
4
1
Order By: Relevance
“…However, Campbell et al (4) demonstrated a significant suppression of ANG II in the kidney of mice with reduced somatic ACE gene expression. The data of Wei et al (43) in the ACE null mice are consistent with our findings of reduced ACE activity, yet similar ANG I and ANG II peptide levels in the diabetic kidney, and suggest that intrarenal ACEindependent pathways for ANG II formation may predominate in the diabetic kidney.…”
Section: Discussionsupporting
confidence: 91%
“…However, Campbell et al (4) demonstrated a significant suppression of ANG II in the kidney of mice with reduced somatic ACE gene expression. The data of Wei et al (43) in the ACE null mice are consistent with our findings of reduced ACE activity, yet similar ANG I and ANG II peptide levels in the diabetic kidney, and suggest that intrarenal ACEindependent pathways for ANG II formation may predominate in the diabetic kidney.…”
Section: Discussionsupporting
confidence: 91%
“…44,45 Radioimmunoassay of relevant peaks revealed detectable levels of angiotensin (Ang) II in all left ventricular (LV) samples examined. Antibodies to Ang II were raised in New Zealand White rabbits immunized against peptide conjugated to poly-L-lysine, as previously described.…”
Section: Tissue Angiotensin II Assaymentioning
confidence: 99%
“…These authors also reported that chymase levels were increased 14-fold in kidney and 1.5-fold in heart of ACE KO mice, in comparison with WT mice, and they suggested that prolonged suppression of ACE activity may lead to the induction of alternate enzymatic pathways of angiotensin II formation in tissue. 2 We and others have shown that ACE inhibition produces marked reduction in angiotensin II levels in blood and tissues of rats and humans. [3][4][5][6] However, ACE inhibition is reported to have variable effects on angiotensin II levels in mice.…”
mentioning
confidence: 92%
“…Many patients receiving ACE inhibitor therapy fail to show reduction in angiotensin II levels, leading to the proposal that alternate enzymes such as chymase may convert angiotensin I to angiotensin II. 1 In support of this proposal, Wei et al 2 reported that although plasma angiotensin II levels of ACE gene knockout (KO) mice were reduced to below the limit of detection, angiotensin II levels in kidney, heart, and lung of ACE KO mice were no different from the levels in wild-type (WT) mice. These authors also reported that chymase levels were increased 14-fold in kidney and 1.5-fold in heart of ACE KO mice, in comparison with WT mice, and they suggested that prolonged suppression of ACE activity may lead to the induction of alternate enzymatic pathways of angiotensin II formation in tissue.…”
mentioning
confidence: 96%